Strategies to Develop Aptamer Probes to Detect MRSA and Study of Antibacterial Activity - Jagath C. Kasturiarachchi (Microbiology Research, 2023)
This study investigated the development of aptamer-based molecular probes to detect Methicillin-Resistant Staphylococcus aureus (MRSA) and evaluated the antibacterial activity. Early detection of MRSA infection will improve patients’ recovery and reduce the cost for treating patients. S. aureus can become resistant to methicillin and other β-lactam antibiotics through the expression of PBP2A protein, which is resistant to the action of methicillin. We have developed two aptamer molecular probes against PBP2A protein and whole bacterial cell (MRSA) under optimized in vitro conditions using SELEX approach. Target aptamer sequences were identified, and chemically synthesized aptamer probes were evaluated using fluorescently-labelled aptamer probes using flow cytometry and confocal imaging. Antibacterial activities of those aptamers were also evaluated using a bacterial killing assay. The results showed that high specific aptamers were developed against purified PBP2A protein. However, these aptamers showed less specificity to detect MRSA under in vitro condition. These aptamers showed no cytotoxic effect on 3T3 cells and no antibacterial activity against MRSA. The results suggested that the specific aptamer development and the in vitro selection methodology require further refinement to improve the diagnostic and therapeutic utility of these aptamers.